2018
DOI: 10.3389/fmicb.2018.02609
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protective Shigella Whole-Cell Vaccine With a Truncated O-Polysaccharide Chain

Abstract: Shigella is a highly prevalent bacterium causing acute diarrhea and dysentery in developing countries. Shigella infections are treated with antibiotics but Shigellae are increasingly resistant to these drugs. Vaccination can be a countermeasure against emerging antibiotic-resistant shigellosis. Because of the structural variability in Shigellae O-antigen polysaccharides (Oag), cross-protective Shigella vaccines cannot be derived from single serotype-specific Oag. We created an attenuated Shigella flexneri 2a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…With this study, using serum from an ETEC controlled human infection study, we have provided an important link between protein glycosylation and the immunogenicity on an established and well investigated non-canonical ETEC antigen. It is possible that YghJ could show the same level of cross-protection as demonstrated in Shigella using the conserved protein outer membrane protein PSSP-1 ( Kim et al, 2018 ). Future investigations will include specific epitope analyses of the glycosylated YghJ and the non-modified protein variant to further study the antigenic potential of O-linked glycosylation.…”
Section: Discussionmentioning
confidence: 97%
“…With this study, using serum from an ETEC controlled human infection study, we have provided an important link between protein glycosylation and the immunogenicity on an established and well investigated non-canonical ETEC antigen. It is possible that YghJ could show the same level of cross-protection as demonstrated in Shigella using the conserved protein outer membrane protein PSSP-1 ( Kim et al, 2018 ). Future investigations will include specific epitope analyses of the glycosylated YghJ and the non-modified protein variant to further study the antigenic potential of O-linked glycosylation.…”
Section: Discussionmentioning
confidence: 97%
“…Although previous studies showed that Akkermansia muciniphila modulates pathways involved in intestinal integrity, basal metabolism and intestinal immunity [ 50 ], our results indicated Akkermansia may reduce the gene expression of the tight junction protein and the level of immunoglobulin resulting in increased intestinal permeability and weakened immune system, which was consistent with the results of sequencing data. Escherichia-Shigella and Bacteroides aggravated the impairment of the gut barrier and bacterial translocation by producing LPS [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…One builds on the PSSP1 antigen strategy in that it involves the unmasking of surface antigens such as PSSP1 on the whole cell by limiting the length of polysaccharide chains synthesized to a single repeating unit. This is the Shigella Truncated Mutant (STM), which utilizes genetically modified (Δwzy) inactivated bacteria retaining only one repeating unit of O antigen chain on the bacterial surface [ 48 ]. The other candidate, ShigETEC, is attenuated by the deletion of the T3SS and is engineered to not express any LPS-O antigens through a targeted deletion of the rfbF gene [ 49 , 50 , 51 ].…”
Section: Shigella Componentmentioning
confidence: 99%
“…A third platform at an earlier stage of development than the previous two is the Shigella truncated mutant (STM) comprised of inactivated Shigella mutants with O-polysaccharide chains truncated to one repeating unit in length [ 48 ]. This, like the ShigETEC, enhances the immunological accessibility of conserved and protective Shigella outer membrane proteins such as PSSP-1 [ 46 ], and may also be a benefit to vectored antigens.…”
Section: Multi-pathogen Strategiesmentioning
confidence: 99%